Effect Of Postharvest Drying Methods On Total Flavonoid Content, Total Phenolic Content, Antioxidant Activity, And Sensory Acceptance Of Coffee Mistletoe (Scurrula ferruginea [Roxb. Ex Jack] Danser) Tea - Nofrizal; Astarie, Shinta Angelia; Putri, Lusia Eka (SITAWA : Jurnal Farmasi Sains dan Obat Tradisional, 2026)
Postharvest drying is a critical step in herbal tea processing as it affects the quality of simplicia, phytochemical content, biological activity, and sensory characteristics of the product. This study aimed to evaluate the effect of postharvest drying methods on total flavonoid content, total phenolic content, antioxidant activity, and sensory acceptance of coffee mistletoe (Scurrula ferruginea [Roxb. ex Jack] Danser) leaf tea. Coffee mistletoe leaves were dried using three different methods: sun drying, oven drying at 40°C, and room-temperature air drying. The dried samples were characterized physicochemically and analyzed for total flavonoid content (AlCl₃ method), total phenolic content (Folin–Ciocalteu method), and antioxidant activity using the DPPH radical scavenging assay (IC₅₀). A sensory acceptance test involving 20 panelists was conducted to evaluate aroma, color, and taste of the tea infusion. The results showed that the drying method significantly affected all evaluated parameters (p < 0.05). Sun drying produced the highest total flavonoid content (2.15 mmol QE/100g sample) and the highest sensory acceptance. Room-temperature drying resulted in the highest total phenolic content (51.41 mmol GAE/100g sample) and the strongest antioxidant activity with the lowest IC₅₀ value (86.4 µg/mL). Oven drying was the most effective in reducing moisture content but led to the greatest losses in flavonoids, phenolics, antioxidant activity, and sensory quality. In conclusion, room-temperature drying is more suitable for maximizing antioxidant potential, whereas sun drying is preferable for producing herbal tea with better consumer acceptance.